Application of a Direct Procedure for the Seismic Retrofit of a R/C School Building Equipped with Viscous Dampers - Trombetti, Tomaso; Palermo, Michele; Dib, Antoine; Gasparini, Giada; Silvestri, Stefano; Landi, Luca (Frontiers in Built Environment, 2015)
Several design methods aimed at sizing the viscous dampers to be inserted in building structures have been proposed in the last decades. Among others, the authors proposed a five-step procedure which guides the practical design from the choice of a target reduction in the seismic response of the structural system (with respect to the response of a structure without any additional damping devices), to the identification of the corresponding damping ratio and the mechanical characteristics of the commercially available viscous dampers. The procedure requires the development of numerical simulations for the evaluations of the peak inter-storey velocity profiles, necessary for the evaluation of the non-linear damping coefficient. In the present paper analytical formulations for the maximum inter-storey velocity are used in order to update the original five-step procedure leading to a direct (i.e. fully analytical) procedure. The direct procedure in finally applied to design the added viscos dampers to be inserted in a real school building in order to improve its seismic capacity